EFFECT OF TIPPING AND FOLIAR APPLICATION OF PROLINE AND BOTMINN PLUS ON VEGETATIVE GROWTH AND LEAVES MINERALS CONTENT OF GRAPEVINE - Mustafa Sh. A.,; Al-Atrushy Sh. M, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted during 2022 in a private vineyard located in Chwarta town northeastern Sulaymaniyah, Kurdistan Region-Iraq, the vineyard was rain-fed cultivation. This research was aimed to investigate the effect of tipping, foliar application of proline (0, 100, and 200 mg.L-1), botminn plus (0, 3, and 6 ml.L-1) and their interaction on vegetative growth parameters, and some leave mineral content. The results showed practicing grapevine's shoot tipping significantly increased single leaf areas, leaf’s chlorophyll content, lateral shoot number, N, P, and K%, except proline content. The foliar application of proline especially at (200 mg.L-1) significantly increased all study characteristics, spraying botminn plus especially at 6 ml.L-1gave the highest value of all study parameters. The triple interaction between tipping, proline, and botminn plus greatly enhanced all traits since tipped vine + 200 mg.L-1 proline + 6 ml.L-1 botminn plus significantly outshine in leaf area, number of lateral shoots, proline content, and N% in leave petiole, whereas the interaction of non-tipped vine + 200 mg.L-1 proline + 6 ml.L-1 botminn plus significantly increased chlorophyll content.